2005
DOI: 10.1097/00008390-200510000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of focal adhesion kinase (FAK) downregulation with FAK antisense oligonucleotides and 5-fluorouracil on the viability of melanoma cell lines

Abstract: Inhibition of focal adhesion kinase (FAK), a non-receptor tyrosine kinase linked to tumour cell survival, causes cell rounding, loss of adhesion and apoptosis in human cancer cell lines. In this study, we tested antisense oligonucleotide inhibitors of FAK, in combination with 5-fluorouracil (5-FU), to increase its sensitivity in human melanoma cell lines. Antisense oligonucleotides directed to the 5' mRNA sequence of FAK and missense control oligonucleotides were used. In BL melanoma cells, treatment with FAK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 33 publications
2
37
0
Order By: Relevance
“…There are previous studies suggesting that FAK is a potential target for therapy in human tumors. Attenuation of FAK in vitro with either a dominant-negative FAK protein (41)(42)(43) or FAK antisense oligonucleotides (44,45) results in cellular rounding, detachment, and significant apoptosis in human tumor cells. Further, down-regulation of FAK in nontransformed fibroblasts (44), normal mammary cells (43), or other normal cell types (46) that express FAK does not result in increased apoptosis in these normal cells.…”
Section: Discussionmentioning
confidence: 99%
“…There are previous studies suggesting that FAK is a potential target for therapy in human tumors. Attenuation of FAK in vitro with either a dominant-negative FAK protein (41)(42)(43) or FAK antisense oligonucleotides (44,45) results in cellular rounding, detachment, and significant apoptosis in human tumor cells. Further, down-regulation of FAK in nontransformed fibroblasts (44), normal mammary cells (43), or other normal cell types (46) that express FAK does not result in increased apoptosis in these normal cells.…”
Section: Discussionmentioning
confidence: 99%
“…N-MYC is reported to be amplified in human melanoma and sarcomas (62) and is associated with poor outcomes (63). It has also been shown that FAK is overexpressed in human sarcoma (16) and melanoma tumors (64,65) and that down-regulation of FAK results in decreased survival in human melanoma cells (66). The regulation of FAK expression by N-MYC in these tumor types has not been investigated but may contribute to the molecular regulation of FAK in these tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of A549 human adenocarcinoma cells with FAK antisense oligonucleotides significantly reduced FAK expression and the concomitant signaling to c-Jun NH 2 -terminal kinase; cell migration and invasion through Matrigel were also inhibited (41). Treatment of melanoma cell lines with FAK antisense oligonucleotides resulted in the decreased expression of FAK and a 2.5-fold increase in cell death compared with treatment with control oligonucleotides (42).…”
Section: Validation Of Fak As a Therapeutic Targetmentioning
confidence: 94%